The “Energetics” of Couples Therapy - Bedrosian, Garet (Bioenergetic Analysis, 2015)
This paper addresses the energetic communication between couples that sometimes derails their connection. Through the integration of Bioenergetic Analysis (BA) and various relationship modalities such as Imago Relationship Theory (IRT) and Emotionally Focused Couples Therapy (EFT) I offer insights and interventions, which may address these nonverbal, energetic disruptions between couples. Examples of sessions with two couples are given using a combination of theories. The paper concludes with themed bodywork techniques for couples addressing issues such as power struggles, negativity, cooperation, connecting/containing and supporting/receiving.